Autofluorescence of liver tissue and bile: Organ functionality monitoring during ischemia and reoxygenation. Issue 5 (12th March 2014) - Croce, Anna C.; Ferrigno, Andrea; Santin, Giada; Piccolini, Valeria M.; Bottiroli, Giovanni; Vairetti, Mariapia
<x xml:space="preserve">Abstract</x> Background and Objective Autofluorescence (AF) based optical biopsy of liver tissue is a powerful approach for the real‐time diagnosis of its functionality. Since increasing attention is given to the bile production and composition to monitor the liver metabolic engagement in surgery and transplantation, we have investigated the bile AF properties as a potential, additional diagnostic parameter. Study Design/Materials and Methods Spectrofluorometric analysis has been performed in real time on a rat liver model of warm ischemia and reperfusion—60 minutes partial portal vein and hepatic artery clamping and subsequent restoration of blood circulation—in comparison with sham operated rats. The AF spectra have been recorded through a single fiber optic probe (366 nm excitation) from both liver tissue and bile, collected from the cannulated bile duct, and analyzed by means of curve fitting procedures. Bile composition has been also analyzed through biochemical assays of bilirubin, total bile acids (TBA) and proteins. Results Both liver and bile AF signal amplitude and spectral shape undergo changes during induction of ischemia and subsequent reperfusion. The liver tissue response is mainly ascribable to changes in NAD(P)H and flavins and their redox state, largely dependent on oxygen supply, and to the decrease of both vitamin A and fatty acid AF contributions. During comparable times, sham operated rat livers undergo smaller alterations in AF spectral shape, indicating a continuous, slight increase in the oxidized state. Bile AF emission shows a region in the 510–600 nm range ascribable to bilirubin, and resulting from the contribution of two bands, centered at about 515–523 and 570 nm, consistently with its bichromophore nature. Variations in the balance between these two bands depend on the influence of microenvironment on bilirubin intramolecular interchromophore energy transfer efficiency and are likely indicating alteration in a bile composition. This event is supported also by changes observed in the 400–500 nm emission region, ascribable to other bile components. Conclusions In parallel with the intratissue AF properties, mainly reflecting redox metabolic activities, the bile AF analysis can provide additional information to assess alterations and recovery in the balance of liver metabolic activities. Lasers Surg. Med. 46:412–421, 2014. © 2014 Wiley Periodicals, Inc.